Birth Weight, Ethnicity, and Exposure to Trihalomethanes and Haloacetic Acids in Drinking Water during Pregnancy in the Born in Bradford Cohort. - Smith,RB; Edwards,SC; Best,N; Wright,J; Nieuwenhuijsen,MJ; Toledano,MB (Environmental Health Perspectives, 2015)
BACKGROUND: Evidence for a relationship between trihalomethane (THM) or haloacetic acid (HAA) exposure and adverse fetal growth is inconsistent. Disinfection by-products exist as complex mixtures in water supplies, but THMs and HAAs have typically been examined separately. OBJECTIVES: We investigated joint exposure at the individual level to THMs and HAAs in relation to birth weight in the multi-ethnic Born in Bradford birth cohort. METHODS: Pregnant women reported their water consumption and activities via questionnaire. These data were combined with area-level THM and HAA concentrations to estimate integrated uptake of THMs into blood and HAA ingestion, accounting for boiling/filtering. We examined the relationship between THM and HAA exposures and birth weight of up to 7,438 singleton term babies using multiple linear regression, stratified by ethnicity. RESULTS: Among Pakistani-origin infants, mean birth weight was significantly lower in association with the highest versus lowest tertiles of integrated THM uptake (e.g., -53.7 g; 95% CI: -89.9, -17.5 for ≥ 1.82 vs. < 1.05 μg/day of total THM) and there were significant trends (p < 0.01) across increasing tertiles, but there were no associations among white British infants. Neither ingestion of HAAs alone or jointly with THMs was associated with birth weight. Estimated THM uptake via showering, bathing, and swimming was significantly associated with lower birth weight in Pakistani-origin infants, when adjusting for THM and HAA ingestion via water consumption. CONCLUSIONS: To our knowledge, this is the largest DBP and fetal growth study to date with individual water use data, and the first to examine individual-level estimates of joint THM-HAA exposure. Our findings demonstrate associations between THM, but not HAA, exposure during pregnancy and reduced birth weight, but suggest this differs by ethnicity. This study suggests that THMs are not acting as a proxy for HAAs, or vice-versa. CITATION: Smith RB